Model-Based Design (MBD) for autonomous underwater vehicle - Mohd Aras, Mohd Shahrieel; Aripin, Muhamad Khairi; Bahar, Mohd Bazli; Tan, Wei Chiang; Ooh, Man Chun; Ho, Gui Yan; Lim, Zhi Han (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This project is to enhanced and upgraded a depth controller for Autonomous Underwater Vehicle (AUV) to submerge precisely at the certain depth. This poster demonstrated an AUV equipped with integrated sensor and depth controller based on the pressure sensing which able to continuously sending the depth data to controller. The depth Simulink Arduino algorithm is implemented on an Arduino Mega using ModelBased Design (MBD) with MATLAB and Simulink. MBD used to model, simulate and verify the Simulink control algorithm after obtained data through open-loop experiment test. Then, it deploys and tests the algorithm on the embedded AUV hardware. The focus was in controlling the AUV vertical trajectory as the AUV tried to remain stationary at the selected depth and consuming its rise time Tr, overshoot Os, and settling time Ts are minimized. The comparative study for the AUV depth-control by On-Off, Proportional Integral Derivative (PID) controller and Fuzzy Logic Controller (FLC) controllers. MBD has faster implementation with fewer coding error when deploy to AUV hardware.